Fatty acid profiles of ecotypes of hyperaccumulator Noccaea caerulescens growing under cadmium stress - Zemanová, Veronika; Pavlík, Milan; Kyjaková, Pavlína; Pavlíková, Daniela (Journal of plant physiology, 2015)
Changes in the fatty acid (FAs) composition in response to the extent of Cd contamination of soils (0, 30, 60 and 90 mg Cd kg(-1)) differed between ecotypes of Noccaea caerulescens originating from France - Ganges, Slovenia - Mežica and Austria - Redlschlag. Mežica ecotype accumulated more Cd in aboveground biomass compared to Ganges and Redlschlag ecotypes. Hyperaccumulators contained saturated fatty acids (SFAs) rarely occurring in plants, as are cerotic (26:0), montanic (28:0), melissic (30:0) acids, and unusual unsaturated fatty acids (USFAs), as are 16:2, 16:3, 20:2 and 20:3. Typical USFAs occurring in the family Brassicaceae, such as erucic, oleic and arachidonic acids, were missing in tested plants. Our results clearly indicate a relationship between Cd accumulation and the FAs composition. The content of SFAs decreased and the content of USFAs increased in aboveground biomass of Ganges and Mežica ecotypes with increasing Cd concentration. Opposite trend of FAs content was determined in Redlschlag ecotype. Linoleic (18:2n-6), α-linolenic (18:3n-3) and palmitic (16:0) acids were found in all ecotypes. The results observed in N. caerulescens ecotypes, showed that mainly Mežica ecotype has an efficient defense strategies which can be related on changes in FAs composition, mainly in VLCFAs synthesis. The most significant effect of ecotype on FAs composition was confirmed using multivariate analysis of variance.
Keywords: 9,12,15-Octadecatrienoic acid; 9,12-Octadecadienoic acid; Thlaspi caerulescens (J. & C. Presl); ekotyp; Brassicaceae; Stress, Physiological; Plant Leaves; Fatty Acids; Metabolic Networks and Pathways; fyziologický stres; Ecotype; Very-long-chain fatty acids; Cadmium; Heavy metals stress; kadmium; mastné kyseliny; Biomass; metabolické sítě a dráhy; listy rostlin; biomasa